O trabalho de enfermeiras/os obstetras na assistência ao parto e nascimento em Goiânia: políticas de humanização, desafios de mercado e relações de trabalho - Silva, Maria Fernandes Gomide Dutra e (2015)
The purpose of this dissertation is to analyze the daily work and the work identities of obstetric nurses engaged on childbirth in the Brazilian city of Goiânia. The emphasis is justified by the fact that since the 1970s the Ministério da Saúde has emphasized the importance of these professionals to the process of humanization of obstetric care in Brazil and for the reversal of cesarean section rate applied in excess in the country. First, it brought back the history of western obstetric care from the Middle Age. Initially, the traditional midwife attended the women in childbirth based on the knowledge inherited from their predecessors and from their own births. With the rise of medieval universities, then began a male-dominated process by formalizing midwifery under the tutelage of medical schools. From the Enlightenment innovations, surgeons begin to map the female organs and childbirth becomes highlighted as a high-risk medical event. This is how the nineteenth century the obstetric care model consolidates around the medical practice founded on the instrumental technology. It is also during this period that modern nursing is established in England and spread to the western world, including Brazil. The midwifery appears initially as professional midwives trained in midwifery schools. Later, this work became the responsibility of nursing colleges, making it a lato sensu specialization. Second, the emphasis was placed on the humanization of childbirth movement in Brazil and the main government programs and policies that focused on attention to prenatal, delivery and postpartum. Finally, thirdly, the highlight was the daily work of the obstetric nurses who work in Goiânia, based on interviews with professionals and also with obstetric doctors and doulas. The study conducted by the author during her graduation in observing the nursing techniques of the Nascer Cidadão Maternity was used as a startin point. It was evident that, although the performance of the professionals in obstetric market is diverse, specialized care is the main element of professional identity category. The approach of the study was primarily qualitative and guided up in addition to the interviews in historical studies related to childbirth in focused studies in public policy and sociology devoted to the study of professional identities. Quantitative data were used to construct their socioeconomic profile. Despite the creation of platforms and professional qualification programs, the rates of cesarean sections and maternal and neonatal morbidity and mortality remain above that recommended by the WHO.